Ratiometric Mass Spectrometry Imaging for Stain-Free Delineation of Ischemic Tissue and Spatial Profiling of Ischemia-Related Molecular Signatures - Wang, Zixuan; Yang, Ran; Zhang, Yaxin; Hui, Xiangyi; Yan, Liuyan; Zhang, Ruiping; Li, Xin; Abliz, Zeper (Frontiers in Chemistry, 2021)
Mass spectrometry imaging (MSI) serves as an emerging tool for spatial profiling of metabolic dysfunction in ischemic tissue. Prior to MSI data analysis, commonly used staining methods, e.g. triphenyltetrazole chloride (TTC) staining need to be implemented on the adjacent tissue for delineating lesion area and evaluating infarction, resulting in extra consumption of tissue sample as well as morphological mismatch. Here, we propose an in situ ratiometric MSI method for simultaneous demarcation of lesion border and spatial annotation of metabolic and enzymatic signatures in ischemic tissue on identical tissue sections. In this method, ion abundance ratio of reactant pair in TCA cycle, e.g. fumarate to malate, is extracted pixel-by-pixel from an ambient MSI dataset of ischemic tissue and used as a surrogate indicator for metabolic activity of mitochondria to delineate lesion area as if the tissue has been chemically stained. This method is shown to be accurate and robust in identifying lesion in brain tissues and tissue samples from different ischemic models including heart, liver and kidney. Furthermore, the proposed method allows screening and predicting metabolic and enzymatic alterations which are related to mitochondrial dysfunction. Being capable of concurrent lesion identification, in situ metabolomics analysis and screening of enzymatic alterations, the ratiometric MSI method bears great potential to explore ischemic damages at both metabolic and enzymatic levels in biological research.